A solar powered handheld plasma source for microbial decontamination applications. (4th August 2016) - Ni, Y; Lynch, M J; Modic, M; Whalley, R D; Walsh, J L
Abstract: A fully portable atmospheric pressure air plasma system is reported to be suitable for the microbial decontamination of both surfaces and liquids. The device operates in quiescent air, and includes an integrated battery which is charged from a solar cell and weighs less than 750 g, making it highly amenable for a wide variety of applications beyond the laboratory. Using particle imaging velocimetry to visualise air flows around the device, the geometric configuration of the plasma generating electrodes was enhanced to induce a gas flow on the order of 0.5 m s −1 directed towards a sample placed downstream, thus improving the transport of plasma generated reactive species to the sample. The microbial decontamination efficiency of the system was assessed using potable water samples inoculated with common waterborne organisms Escherichia coli and Pseudomonas fluorescens . The reduction in the number of microorganisms was found to be in the range of 2–8 log and was strongly dependent on the plasma generation conditions.